THE USE OF CYCLONE COAL BURNER TO SUBSTITUTE OIL BURNER IN ALUMINUM SMELTER USING REVERBERATORY FURNACE - SUMARYONO SUMARYONO (Puslitbang tekMIRA, 2008)
The increasing of oil price forces the industries to alter their fuel from oil into a cheaper fuel. Undoubt- edly, coal is a promising energy alternative in Indonesia. To save the cost, altering the fuel oil into coal in industries may be accomplished just by altering the oil burner with coal burner, therefore the exist- ing equipment still can be used without much modification. The coal combustor employed should have nearly the same characteristic with the oil combustor, so that the performance of the kiln or other equipment served by the combustor is not change significantly. R & D Centre for Mineral and Coal Technology (TekMIRA) has developed cyclone combustor for coal with particle size of less than 30 mesh. The combustion is stable at the rate of 50 – 180 kg/hr coal with excess combustion air of 22 – 26%. The length of cyclones is ranged from 120 up to 220 cm, the internal diameter is 60 up to 80 cm and the combustion temperature is 1200 up to 1325°C. This combustor characteristics are nearly the same with oil combustor such as: the combustion flame may be directed; high intensity combustion, long flame; and it is not difficult to match the energy output of previous oil combustor. In this experiment the cyclone combustor was used to replace the oil combustor in a reverberatory furnace to refine aluminum from aluminum scrap by melting the material at 1000 – 1060°C. For 500 kg aluminum, the oil consumption was 47.5 litre for 2.5 hour or the average was 19 lt/hr and the energy efficiency was 29.2%. Using high ash bituminous coal with cyclone burner, the coal consumption was 129 kg for 1.8 hour or the average was 71.6 kg/hr and the energy efficiency was 17.9%. A higher efficiency was obtained by using low ash sub bituminous coal, that the coal consumption was 82 kg for 81 minutes or the average was 60 kg/hr and the energy efficiency was 29.0%. Therefore it is a good opportunity for coal to substitute fuel oil in this reverberatory furnace and many other oil fuelled processes such as in boiler, lime calcination, mineral drying etc.